ASSESSING MULTIDIMENSIONAL SCALE OF LOW SELF-CONTROL IN MALAYSIAN PROPERTY CRIMES PRISONERS - Mohd Sobhi Ishak; Zafari Zulkifli; Mohd Mahadee Ismail; Ahmad Zul Hakimi Hassim, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The increasing incidence of criminal and delinquent behaviour has received a lot of attention. The Low Self-Control Scale (LSCS) developed by Grasmick et al. (1993) has been significant in our understanding of the role of self-control in that behaviour. The purpose of this study is to look into the psychometric properties of the Malay language modified multidimensional LSCS among 181 property crime convicts in Malaysia prisoner. The validity and reliability of the LSCS second-order reflection measurement model were investigated using the partial least square structural equation modelling (PLS-SEM) method. The findings demonstrate that the six LSCS constructs (temper, easy tasks, self-centered, risk seeking, physicality, and impulsivity), as well as the 23 indicators, can explain the concept of low self-control. This research proved the construct reliability, discriminant validity, and convergent validity of the LSCS’s Malay version. In addition, this research also demonstrated that prisoners disclosed themselves high on each LSCS’s constructs, having the highest ratings on impulsivity and the lowest on temper. In conclusion, the psychometric evidence of LSCS in this study will be catalyzed for future studies of individual self-control in delinquent or criminal behavior.